Attachment theory and research : new directions and emerging themes - Simpson, Jeffry A.; Rholes, W. Steven (William Steven) (New York : The Guilford Press, 2015)
'This volume showcases the latest theoretical and empirical work from some of the top scholars in attachment. Extending classic themes and describing important new applications, the book examines several ways in which attachment processes help explain how people think, feel, and behave in different situations and at different stages in the life cycle. Topics include the effects of early experiences on adult relationships; new developments in neuroscience and genetics; attachment orientations and parenting; connections between attachment and psychopathology, as well as health outcomes; and the relationship of attachment theory and processes to clinical interventions. Key Words/Subject Areas: attachment research, attachment security, attachment theory, couple interventions, developmental psychology, dyadic regulation process, emotion, parenting, psychopathology, relationships, romantic functioning, romantic attachment Audience: Researchers and students in social, developmental, personality, and clinical psychology. Serves as a primary or supplemental text in advanced undergraduate or graduate courses on attachment, close relationships, interpersonal processes, and family relationships'--
Introduction : new directions and emerging themes in attachment theory and research / W. Steven Rholes and Jeffry A. Simpson -- Early attachment experiences and romantic functioning : developmental pathways, emerging issues, and future directions / R. Chris Fraley and Glenn I. Roisman -- The neuroscience of attachment : using new methods to answer old (and new) questions / Omri Gillath -- Fooled around and fell in love : the role of sex in adult romantic attachment formation / Vivian Zayas, Sarah Merrill, and Cindy Hazan -- Stress and attachment / Lisa M. Diamond -- Boosting attachment security in adulthood : the'broaden-and-build' effects of security-enhancing mental representations and interpersonal contexts / Mario Mikulincer and Phillip R. Shaver -- Attachment and dyadic regulation processes / Nickola C. Overall and Edward P. Lemay, Jr. -- On the convergence of sexual urges and emotional bonds : the interplay of the sexual and attachment systems during relationship development / Gurit E. Birnbaum -- An attachment-theoretical perspective on optimal dependence in close relationships / Brooke C. Feeney, Meredith Van Vleet, and Brittany K. Jakubiak -- Adult attachment style and parenting / Jason D. Jones, Jude Cassidy, and Phillip R. Shaver -- Attachment theory in organizational settings / Ramona L. Paetzold -- Health and attachment processes / Paula R. Pietromonaco, Cassandra C. DeVito, Fiona Ge, and Jana Lembke -- Attachment and aged care / Gery C. Karantzas and Jeffry A. Simpson -- Psychopathology and attchment / Tsachi Ein-Dor and Guy Doron -- Attachment-related preventive interventions / Mary Dozier and Caroline K. P. Roben -- Attachment : a guide to a new era of couple interventions / Susan M. Johnson, Marie-France Lafontaine, and Tracy L. Dalgleish.
Machine generated contents note: Introduction: New Directions and Emerging Themes in Attachment Theory and Research, W. Steven Rholes & Jeffry A. Simpson1. Early Attachment Experiences and Romantic Functioning: Developmental Pathways, Emerging Issues, and Future Directions, R. Chris Fraley & Glenn I. Roisman2. The Neuroscience of Attachment: Using New Methods to Answer Old (and New) Questions, Omri Gillath3. Fooled Around and Fell in Love: The Role of Sex in Adult Romantic Attachment Formation, Vivian Zayas, Sarah Merrill, & Cindy Hazan4. Stress and Attachment, Lisa M. Diamond5. Boosting Attachment Security in Adulthood: The'Broaden-and-Build' Effects of Security-Enhancing Mental Representations and Interpersonal Contexts, Mario Mikulincer & Phillip R. Shaver6. Attachment and Dyadic Regulation Processes, Nickola C. Overall & Edward P. Lemay, Jr.7. On the Convergence of Sexual Urges and Emotional Bonds: The Interplay of the Sexual and Attachment Systems during Relationship Development, Gurit E. Birnbaum8. An Attachment Theoretical Perspective on Optimal Dependence in Close Relationships, Brooke C. Feeney, Meredith Van Vleet, & Brittany K. Jakubiak9. Adult Attachment Style and Parenting, Jason D. Jones, Jude Cassidy, & Phillip R. Shaver10. Attachment Theory in Organizational Settings, Ramona L. Paetzold11. Health and Attachment Processes, Paula R. Pietromonaco, Cassandra C. DeVito, Fiona Ge, & Jana Lembke12. Attachment and Aged Care, Gery C. Karantzas & Jeffry A. Simpson13. Psychopathology and Attachment, Tsachi Ein-Dor & Guy Doron14. Attachment-Related Preventive Interventions, Mary Dozier & Caroline Roben15. Attachment: A Guide to a New Era of Couple Interventions, Susan M. Johnson, Marie-France Lafontaine, & Tracy L. DalgleishIndex.
Includes bibliographical references and indexes.
Keywords: Object Attachment